AtNIGT1/HRS1 integrates nitrate and phosphate signals at the Arabidopsis root tip - Medici, Anna (Nat Commun, 2015)
Nitrogen and phosphorus are among the most widely used fertilizers worldwide. Nitrate (NO(3)(−)) and phosphate (PO(4)(3−)) are also signaling molecules whose respective transduction pathways are being intensively studied. However, plants are continuously challenged with combined nutritional deficiencies, yet very little is known about how these signaling pathways are integrated. Here we report the identification of a highly NO(3)(−)-inducible NRT1.1-controlled GARP transcription factor, HRS1, document its genome-wide transcriptional targets, and validate its cis-regulatory-elements. We demonstrate that this transcription factor and a close homolog repress primary root growth in response to P deficiency conditions, but only when NO(3)(−) is present. This system defines a molecular logic gate integrating P and N signals. We propose that NO(3)(−) and P signaling converge via double transcriptional and post-transcriptional control of the same protein, HRS1